Removal of Reactive Green Dye from Textile Waste Water by Photo Fenton Process: Modeling, Kinetic, and Thermodynamic. - Jabar, Tabarek Abdulsajad; Al-zobai, Khalid M. Mousa (Al-Nahrain Journal for Engineering Sciences, 2021)
This work investigated the removal of the reactive green (R.G) dye from wastewater using the photo-Fenton process. Batch experiments were carried out to research the role of the Impacts of operating parameters. The dosage of H2O2; dosage Fe+2; pH; temperature, and irradiation time were examined. Maximum decolorization efficiencies green dye were achieved at the [H2O2]=100 ppm; [Fe2+]=20 ppm; pH 3; temperature=56 °C and irradiation time=90 min. This research focuses on modeling, kinetics and thermodynamics of the removal of pollutant (reactive green dye) of water. The results showed that the decolorization kinetic of R.G followed pseudo-first-order reaction kinetic. Also the thermodynamic parameters ?G?, ?H? and ?S? were determined using the Van’t Hoff equation for the oxidation processes. The changes in Gibbs free energy showed the oxidation process under normal conditions is non-spontaneous.